The Relationship Between Teacher Performance and Teacher Digital Literacy with the Implementation of Online Learning - Baso Intang Sappaile; Andi Tenri Abeng; Nuridayanti Nuridayanti (Yayasan Adra Karima Hubbi, 2023)
Background. The study population was all teachers of State Senior High Schools in Gowa Regency, while the samples were all teachers of State Senior High School 10 and State Senior High School 14 in Gowa Regency Purpose. This study aims to determine whether there is a relationship between teacher performance and digital literacy with the implementation of online learning for teachers of SMA Negeri Gowa Regency, both jointly and separately Method. Data was obtained by giving teacher performance scales, teacher digital literacy, and online learning implementation scales. Results. Data were analyzed quantitatively, namely by using multiple linear regression analysis. The conclusions in this study are: 1) teacher performance and teacher digital literacy together have a relationship with the implementation of online learning, 2) teacher performance has no relationship with the implementation of online learning, and 3) teacher digital literacy has a relationship with the implementation of teacher online learning Gowa Regency Public High School. Conclusion. The conclusion of this study is to find out whether there is a relationship between teacher performance and digital literacy with the implementation of online learning in public high school teachers in Gowa Regency, both together and separately.